JA 'The Boy' from Louisiana Story - Chris Hainstock (2014)
'JC' Joseph Boudreaux was chosen as a young by to appear in Robert Flaherty's film Louisiana Story,Louisiana Story (1948) is a 78-minute black-and-white American film. Although the events and characters depicted are fictional, it is often misidentified as a documentary film, when in fact, it is a docufiction. The script was written by Frances H. Flaherty and Robert J. Flaherty, directed by Robert J. Flaherty, and was commissioned by the Standard Oil Company.The boy, named in the film as Alexander Napoleon Ulysses Le Tour but in the credits just identified as the boy, was played by Joseph Boudreaux. The film was photographed by Richard Leacock and edited by Helen van Dongen, who were also the associate producers. Original release was through independent film distributor Lopert Films.Originally interviewed as part of the film 'A Boatload of Wild Irishman' Distributed by Icarus Films (AKA 'The Wandering Irishman')A BOATLOAD OF WILD IRISHMEN includes testimony from Flaherty himself as well as contributions from amongst others, Richard Leacock - cameraman on 'Louisiana Story' (1948) and father of the contemporary hand-held documentary style, Martha Flaherty - Flaherty's Inuit granddaughter, George Stoney - documentary filmmaker and professor at New York University, Sean Crosson - film scholar at the Huston School of Film, Jay Ruby - anthropologist and film scholar at Temple University, and Deirdre Ni Chonghaile - musician and folklorist from Arainn, as well as telling interviews with the people whose parents and grandparents Flaherty put onto the cinema screens of the world: Inuit, Samoans and, of obvious personal interest to the Irish filmmakers, the 'wild men' of Aran.Originally interviewed as part of the film 'The Wandering Irishman' Distributed by Icarus Films